محددات مخالفة معايير النزاهة الأكاديمية لدى طلاب المرحلة الجامعية وما فوق الجامعية في بعض الجامعات السعودية - الحربي، مروان بن علي (جائزة راشد بن حميد للثقافة والعلوم, 2017)
The present study aimed to identify the level of commitment to integrity and academic with students Undergraduate and Graduate students in some Saudi universities (King Abdul Aziz University / and ،Umm Al Qura University / Taibah University) to reveal the nature of the relationship between academic integrity and all of the moral responsibility and achievement ،and self-efficiency academic and cognitive ، and learning strategies،motivation in addition to determining ،testing and GPA concern how different level of commitment to integrity and academic according to the variation of both and the ،undergraduate (BA / Diploma / Masters) the study also ،university to which they belong aimed to detect for the best predictors of academic integrity by knowing the independent variables under study. The study sample included 357 male and female students who are studying undergraduate and study results indicated: Rising ،and postgraduate violation of academic integrity standards indicators and to the ،in general and on the six sub-dimensions lack of statistically significant differences in commitment to academic integrity standards among students stage level university and above the and to ،university due to the University of difference the presence of a statistically significant difference between the students and the students undergraduate and above the university on five sub-dimensions of in addition to a ،academic integrity standards statistically significant difference on the total score of the questionnaire is due to the difference in and to the presence of correlation ،undergraduate between academic integrity and all of the moral and cognitive ،responsibility and self-efficacy testing and learning strategies for anxiety and as well as it can ،achievement motivation and GPA be interpreted approximately (56.5%) of the variance on the integrity variable Academy with ،students undergraduate and above the university and it knowledge of moral responsibility towards and learning strategies and achievement ،learning motivation and self-efficiency except cognitive test anxiety and GPA.
هدفت الدراسة الحالية إلى التعرف على مستوى الالتزام بالنزاهة الأكاديمية لدى طلاب وطالبات المرحلة الجامعية وما فوق الجامعية في بعض الجامعات السعودية) جامعة الملك عبد العزيز، جامعة أم القرى، جامعة طيبة) وإلى الكشف عن طبيعة العلاقة بين النزاهة الأكاديمية وكل من المسؤولية الأخلاقية والكفاءة الذاتية الأكاديمية، ودافعية الإنجاز، واستراتيجيات التعلم، وقلق الاختبار المعرفي والمعدل التراكمي، بالإضافة إلى تحديد مدى اختلاف مستوى الالتزام بالنزاهة الأكاديمية طبقاً لاختلاف كل من المرحلة الجامعية (بكالوريوس، دبلوم، الماجستير(، والجامعة التي ينتمون إليها، والكشف عن أفضل المنبئات بالنزاهة الأكاديمية من خلال معرفة المتغيرات المستقلة محل الدراسة . وشملت عينة الدراسة ( 357 ) طالباً وطالبة ممن يدرسون بالمرحلة الجامعية وما فوق الجامعية، وأشارت نتائج الدراسة إلى: ارتفاع مؤشرات انتهاك معايير النزاهة الأكاديمية بشكل عام وعلى أبعادها الفرعية الستة، وإلى عدم وجود فروق دالة إحصائياً في مستوى الالتزام بمعايير النزاهة الأكاديمية لدى طلاب وطالبات المرحلة الجامعية وما فوق الجامعية تعزى إلى اختلاف الجامعة، وإلى وجود فرق دال إحصائياً بين الطلاب وطالبات المرحلة الجامعية وما فوق الجامعية على خمسة أبعاد الفرعية معايير النزاهة الأكاديمية، بالإضافة إلى وجود فرق دال إحصائياً على الدرجة الكلية للاستبيان يعزى إلى اختلاف المرحلة الجامعية، وإلى وجود علاقة ارتباطيه بين النزاهة الأكاديمية وكل من المسؤولية الأخلاقية والكفاءة الذاتية، وقلق الاختبار المعرفي واستراتيجيات التعلم ودافعية الإنجاز والمعدل التراكمي، بالإضافة إلى أنه يمكن تفسير ما يقارب (%56.5 ) من التباين على متغير النزاهة الأكاديمية لدى طلاب وطالبات المرحلة الجامعية وما فوق الجامعية، وذلك بمعرفة المسؤولية الأخلاقية نحو التعلم، واستراتيجيات التعلم ودافعية الإنجاز والكفاءة الذاتية) عدا قلق الاختبار المعرفي و المعدل التراكمي).
Keywords: النزاهة الأكاديمية -- طلاب الجامعات -- المعايير -- الجامعات السعودية -- المسؤولية الأخلاقية -- المخالفات السلوكية -- الكفاءة الذاتية